OPTIMIZING WOUND CARE: THE IMPORTANCE OF NEGATIVE PRESSURE WOUND THERAPY FOR VARIOUS ETIOLOGIES AND LOCALIZATIONS - Madalina Cristina Fotea; Dorin Sumanaru; Dan Cristian Moraru; Stefana Luca; Oxana Madalina Grosu; Alexandru Tomac; Teodor Rosca; Laura Bozomitu; Alexandru Amarandei; Mihaela Pertea (Romanian Society of Oral Rehabilitation, 2023)
Aim of the study This study aims to investigate the efficacy of Negative Pressure Wound Therapy (NPWT) in optimizing wound care across a diverse range of etiologies and localizations. Material and methods A study of 97 patients with various wound etiologies and localizations was conducted. NPWT was meticulously applied according to established protocols, with treatment parameters being methodically documented. Results NPWT exhibited substantial efficacy in promoting wound healing across varied etiologies and localizations. Acute wounds demonstrated reduced dimensions alongside enhanced granulation tissue formation. In parallel, chronic wounds exhibited improved wound bed preparation and diminished bacterial colonization. Conclusions NPWT proves to be a versatile and effective treatment modality for optimizing wound care across different etiologies and localizations. Its ability to improve wound healing outcomes, by enhancing tissue perfusion, reducing edema, and modulating inflammation, positions NPWT as a valuable tool in comprehensive wound management strategies. Its ability to enhance tissue perfusion, mitigate edema, and modulate inflammation underscores its value as a pivotal tool within comprehensive wound management strategies.